Quranic Memorization Obstacles and Pedagogical Intervention Strategic among Students of Tahfidz Institution - Annisah Safitri; Mahasri Shobahiya (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to analyze the challenges faced by female students from non-Islamic educational backgrounds in achieving Quranic memorization targets at Rumah Setia Putri Tahfidz Boarding School, Sukoharjo. The primary problem lies in the significant disparity in initial Quranic literacy, which hinders students from secular schools from meeting the standardized memorization pace of the institution. This research employs a qualitative descriptive approach to explore the lived experiences and pedagogical adaptations of these students. Data were collected through in-depth interviews, field observations, and documentation reviews involving students and tahfidz instructors. The gathered data were analyzed using thematic analysis, involving data reduction, display, and conclusion drawing to ensure interpretive validity. The findings indicate that students from non-Islamic backgrounds often struggle with basic recitation rules (tajwid), with some even requiring foundational instruction starting from the Iqra’ level. This lack of prior religious education causes a noticeable achievement gap compared to peers from Islamic elementary schools. However, intensive guidance through tahsin and talaqqi sessions has proven effective in helping these students bridge the competency gap. Furthermore, the implementation of personalized memorization targets allows students to progress according to their individual capacities without excessive psychological pressure. Internal obstacles such as laziness, perceived difficulty of memorization, and lack of focus remain prevalent challenges. Future research should investigate the long-term retention rates (muraja’ah) of students from secular backgrounds compared to those with formal religious foundations.